Chymase-Cre; Mcl-1fl/fl Mice Exhibit Reduced Numbers of Mucosal Mast Cells - Luo, Ying; Meyer, Nicole; Jiao, Qingqing; Scheffel, Jörg; Zimmermann, Carolin; Metz, Martin; Zenclussen, Ana; Maurer, Marcus; Siebenhaar, Frank (Frontiers in Immunology, 2019)
Mast cells (MCs) are considered as key effector cells in the elicitation of allergic symptoms and they are essential players in innate and adaptive immune responses. In mice, two main types of MCs have been described: connective tissue MCs (CTMCs) and mucosal MCs (MMCs). However, little is known about the biological functions of MMCs, which is due to the lack of suitable models to investigate MMCs in vivo. Here, we aimed to generate a mouse model selectively deficient in MMCs. It has been previously described that Cre expressed under the control of the baboon α-chymase promotor is predominantly localized in MMCs. Therefore, we mated α-chymase-Cre transgenic mice with mice bearing a floxed allele of the myeloid cell leukemia sequence 1 (Mcl-1). Mcl-1 encodes for an intracellular antiapoptotic factor in MCs, hence a selective reduction in MMCs was expected. Our results show that this new mouse model contains markedly reduced numbers of MMCs in mucosal tissues, whereas numbers of CTMCs are normal. Thus, Chm-Cre; Mcl-1fl/fl mice are a useful tool for the investigation of the pathophysiological functions of MMCs in vivo.